Study on Advanced Technologies in Professional Sports Performance - Dr. Vandana Gupta (International Journal of Engineering and Management Research, 2020)
Technology plays a significant role in making modern life simple and effective. Technology has had a significant impact on sports, science, and many other facets of daily life. The market for the sports business has grown along with popularity, and so has the necessity for technological research. The primary goal of this academic qualitative study was to examine how modern technology affects athletic performance. The role of particular games and sports is often emphasized in the discussion of various technological equipment. For the purpose of gathering data for this systematic qualitative study, an exhaustive online and offline search technique was used. The current researcher discovers a variety of technological tools now used in the world of games and sports. The researchers concur that these technological advancements raise performance scores and simplify games. Making the right choice when selecting the technology is essential for performance development since, in the modern environment, dealing with and managing players is a challenging process. Last but not least, the researcher also thought that a variety of systematic reviews could more precisely emphasize the impact of technology on sports performance.